The effect of AKT inhibition in α-synuclein-dependent neurodegeneration - Ranxhi, Bedri; Bangash, Zoya R.; Chbihi, Zachary M.; Todi, Sokol V.; LeWitt, Peter A.; Tsou, Wei-Ling (Frontiers in Molecular Neuroscience, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder affecting millions of individuals worldwide. A hallmark of PD pathology is the accumulation of α-synuclein (α-Syn), a small protein known to support neuronal development and function. However, in PD, α-Syn cumulatively misfolds into toxic aggregates that disrupt cellular processes and contribute to neuronal damage and neurodegeneration. Previous studies implicated the AKT signaling pathway in α-Syn toxicity in cellular models of PD, suggesting AKT as a potential therapeutic target. Here, we investigated the effect of AKT inhibition in a Drosophila model of synucleinopathy. We observed that administration of the AKT inhibitor, A-443654 led to mild improvements in both survival and motor function in flies expressing human α-Syn. Genetic studies revealed that reduction of AKT levels decreased α-Syn protein levels, concomitant with improved physiological outcomes. The protective effects of AKT reduction appear to operate through the fly ortholog of NF-κB, Relish, suggesting a link between AKT and NF-κB in regulating α-Syn levels. These findings highlight the AKT cascade as a potential therapeutic target for synucleinopathies and provide insights into mechanisms that could be utilized to reduce α-Syn toxicity in PD and related disorders, such as multiple system atrophy.